Pediatric polypectomy via an open approach in a resource limited setting - Anjila Thapa; Niharika Khanal; Dinesh Koirala; Naveen Bhatta (Elsevier, 2021)
Juvenile polyp located in the recto sigmoid junction is a common pediatric condition. Albeit, being a common occurrence, in resource limited setting the diagnoses of polyp and subsequent polypectomy still possesses major challenges. The case presented here is of a 3-year-old boy who presented with rectal bleeding for 8 months and in whom the diagnoses of rectal polyp had been established. After failed attempts to remove the polyp colonscopically, an open approach was adopted for the removal of the polyp. The two main factors that hindered the more preferred colonoscopic method was the size of the polyp (3cm*3cm), and the setting we are in. Therefore, in conclusion we think an open approach should be on top of the list for removal of rectal polyp in children with large polpys in settings like ours.